The N-Glycosylation of Mouse Immunoglobulin G (IgG)-Fragment Crystallizable Differs Between IgG Subclasses and Strains - de Haan, Noortje; Reiding, Karli R.; Krištić, Jasminka; Hipgrave Ederveen, Agnes L.; Lauc, Gordan; Wuhrer, Manfred (Frontiers in Immunology, 2017)
N-linked glycosylation of the Fc-region of IgG is known to have a large influence on the activity of the antibody, an effect reported to be IgG subclass-specific. This situation applies both to humans and mice. The mouse is often used as experimental animal model to study the effects of Fc-glycosylation on IgG effector functions, and results are not uncommonly translated back to the human situation. However, while human IgG Fc-glycosylation has been extensively characterized in both health and disease, this is not the case for mice. To characterize the glycosylation profile of murine IgG-Fc and in addition evaluate the systematic glycosylation differences between mouse strains, sexes and IgG subclasses, we used nanoLC-MS(/MS) to look at the subclass-specific IgG Fc-glycopeptides of male and female mice from the strains BALB/c, C57BL/6, CD-1 and Swiss Webster. The structural analysis revealed the presence of predominantly fucosylated, diantennary glycans, with varying amounts of galactosylation and α2,6-sialylation. In addition, we report glycosylation features not previously reported in an Fc-specific way on murine IgG, including monoantennary, hybrid, and high mannose structures, as well as diantennary structures without a core fucose, with a bisecting GlcNAc, or with α1,3-galactosylation. Pronounced differences were detected between strains and the IgG subclasses within each strain. Especially the large spread in galactosylation and sialylation levels found between both strains and subclasses may vastly influence IgG effector functions. Mouse strain-based and subclass-specific glycosylation differences should be taken into account when designing and interpreting immunological and glycobiological mouse studies involving IgG effector functions.